The Lifestyle of Hip Life Musicians and Its Influence on the Ghanaian Youth - Amos, Patricia Mawusi; Mensah, Joyce (Advances in Social Sciences Research Journal, 2015)
This study sort to find out some of the negative effect the lifestyle of hip life musicians have on Ghanaian youth in two senior high schools in the Ashanti and Central regions of Ghana. Through quota sampling procedure twenty students were selected from the two schools. The research instrument used was open- ended questionnaire. Data collected was analyzed thematically. The findings revealed that most youth are into hip life because they believe it is modern fashioned. Also, the lyrics and rhythms are consistent with the jargons they use as well as the dances they do. A few mentioned that the lifestyle of the musicians have brought nothing but indiscipline and irresponsible behaviour among the youth and this can be seen in the way they dress, talk and even think. Similarly, the lifestyle of these musicians have greatly influenced Ghanaian culture in that most of the youth due to the lifestyle of these musicians have adopted foreign cultures which is making it difficult for the youth to adopt to Ghanaian culture. The researchers therefore recommend that the younger generation of musicians should be made aware of how their lifestyle is affecting the youth and Ghanaian culture negatively. Also there should be strict rules and regulations to govern the general lifestyle of all musicians as well as their lyrics and video clips. Hip life musicians should be educated to serve as positive role models for the youth since majority of them are in the age group of the youth.